2001
DOI: 10.1002/ajmg.1589
|View full text |Cite
|
Sign up to set email alerts
|

Inv dup del (1)(pter?q44::q44?q42:) with the classical phenotype of trisomy 1q42-qter

Abstract: We report on a girl with a trisomy 1q42-q44 due to an inverted duplication of this region, associated with a terminal deletion of the long arm of the rearranged chromosome 1. Both the large duplication (more than 30 cM) and the small deletion were detected by FISH. Complete karyotype was: (46,XX, inv dup(1)(q44q42).ish(dup del 1)(q44q42)(D1S446x2, D1S423x2, tel1q-). The phenotype of the patient is characterized by macrocephaly with prominent forehead, downslanting palpebral fissures, micrognathia, and psychomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 12 publications
4
38
0
Order By: Relevance
“…This patient has a karyotype similar to that previously described by De Brasi et al (2001) in a case with a classical phenotype of trisomy 1q42 → qter. According to Bartsch et al (2001) such rearrangements can be classified to the group IV of partial trisomy 1q carriers.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This patient has a karyotype similar to that previously described by De Brasi et al (2001) in a case with a classical phenotype of trisomy 1q42 → qter. According to Bartsch et al (2001) such rearrangements can be classified to the group IV of partial trisomy 1q carriers.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, three of the six patients (Mewar et al, 1994;Bartsch et al, 2001) carry other, additional chromosomal imbalances in addition to a duplication in 1q, making the specific influence of this chromosomal region for assessment of the clinical phenotype more difficult. Accordingly, cases described by Mewar et al (1994) andDe Brasi et al (2001) show subterminal deletions -while case B described here does not.…”
Section: Discussionmentioning
confidence: 85%
“…The studies on the inv dup(8p), a recurrent rearrangement associated with a rather characteristic syndrome, 9 revealed that it derives by nonallelic homologous recombination between lowcopy repeats. 7,8,10 Other examples of inv dup are those concerning 1q, 11,12 24 suggesting that the mechanism responsible for the inv dup(8p) can be generalized to all inverted duplications. In our inv dup(8q) case, we were not able to find any associated deletion distal to the last duplicated clone RP5-1109M23 nor any segmental duplication responsible for the occurrence of the inv dup(8q).…”
Section: Discussionmentioning
confidence: 99%
“…The best-known case is that of the inv dup(8p). 1,2 Other examples are those concerning 1q, 3,4 2q, 5 3p 6,7 4p, 8 5p, 9,10 9p, 11 10p and 10q, 12 18p 13 18q, 14 21q 15 and the X;X or the Y;Y rearrangements leading to duplications of parts of the short or the long arm with concomitant deletion. 16 It has been assumed 1,5 that the first product of the abnormal meiotic recombination on the basis of this type of rearrangement was a dicentric chromosome, either p-qHq-p or q-pHp-q.…”
Section: Introductionmentioning
confidence: 99%